De novo variants in SNAP25 cause an early-onset developmental and epileptic encephalopathy. - Klöckner, Chiara; Sticht, Heinrich; Zacher, Pia; Popp, Bernt; Babcock, Holly E; Bakker, Dewi P; Barwick, Katy; Bonfert, Michaela V; Bönnemann, Carsten G; Brilstra, Eva H; Chung, Wendy K; Clarke, Angus J; et al. (Genet Med, 2021)
PURPOSE: This study aims to provide a comprehensive description of the phenotypic and genotypic spectrum of SNAP25 developmental and epileptic encephalopathy (SNAP25-DEE) by reviewing newly identified and previously reported individuals. METHODS: Individuals harboring heterozygous missense or loss-of-function variants in SNAP25 were assembled through collaboration with international colleagues, matchmaking platforms, and literature review. For each individual, detailed phenotyping, classification, and structural modeling of the identified variant were performed. RESULTS: The cohort comprises 23 individuals with pathogenic or likely pathogenic de novo variants in SNAP25. Intellectual disability and early-onset epilepsy were identified as the core symptoms of SNAP25-DEE, with recurrent findings of movement disorders, cerebral visual impairment, and brain atrophy. Structural modeling for all variants predicted possible functional defects concerning SNAP25 or impaired interaction with other components of the SNARE complex. CONCLUSION: We provide a comprehensive description of SNAP25-DEE with intellectual disability and early-onset epilepsy mostly occurring before the age of two years. These core symptoms and additional recurrent phenotypes show an overlap to genes encoding other components or associated proteins of the SNARE complex such as STX1B, STXBP1, or VAMP2. Thus, these findings advance the concept of a group of neurodevelopmental disorders that may be termed "SNAREopathies."
Keywords: Brain Diseases; Child, Preschool; Epilepsy; Humans; Intellectual Disability; Neurodevelopmental Disorders; Phenotype; Synaptosomal-Associated Protein 25